Corporate failure prediction: the impact of board gender diversity, corporate governance and firm characteristics on public listed companies in Malaysia (individual management project) - Cheah, Weng Hon (2018)
This studyanalyses the impacts of three attribute groups-board gender diversity, corporate governance and firm characteristics related to financial distress incident of companies listed in Bursa Malaysiamain market from 2010 to 2016. Anoverview on serial of theories behind those three variable groups to find empirical evidence and explanation for relationship between board gender diversity, corporate governance and firm characteristics, and corporate financial failure. The study presents empirical research using Logit and Probit model, in analyzing60 matched pairs of financial distressed and non-financial distressed Malaysian companies. The results show a positiverelationship between percentage of outside directors and financial failure. Debt ratio of financial distressed companies were higher than those financially healthy companies. Financially distressed companies are negatively correlated with ROA. No significant relationship is found between genderdiversity, CEO duality, board size, current ratio, firm age, firm size,and financial distress. The findings do not show strongevidence to supportthe agency theory,resource-dependence theory,stewardship theory, “liability of newness” and liability of smallnessconcept. Those neutral results are argued on account of two reasons –firstly, a lack of critical mass in term of female participation in the boards, in order to create significant impacts on the outcome of companies,secondly, there is offset between reasonable features outlined by agency theory, resource dependency theory and stewardship theorywhich lead to a “no effect” results, asproposed by Carter et al. (2010). This study argues that cronyism behavior in the appointment of outside directors may take place among financially distressed companies in this country. This study supports the findings of previous researches to continuously emphasize on financial ratios in predicting corporate failure, with new evidence to raise the awareness of researchers and practitioners, especially the policymakers to consider the underlying motivation in determining a balanced insiders-outsiders structure. Overall takeaway from this study is the recommendation of multi-theoretical approach or contingency theory shall be considered by researches, practitioners and regulators in determining the causes of financial distress of public listed companies. As summarized, this paper achieves the objective by working out a practical corporate failure prediction model. The findings and theoretical explanation developed are expected to contribute positively to future works and decision making of academics, policy makers and investors (including shareholders and debtholders). Among limitations recognized here are shortcoming of Logit and Probit as static regression model, and inaccessibility and unavailability of data and information. Therefore, this study further recommends the application ofdynamic regression model to investigate time serial data, such as comparison of pre-failure and post-failure data. The future research works also could focus on topics linking the same or new attributes and financial failure upon implementation of several new regulations, and to extend the scope to other organizational level (top management team, senior management and staff) within a company.